Editorial: Current challenges for spatial planning in EU country systems - Nowak, Maciej Jacek. Autor (IGiPZ PAN, 2024)
This article presents the key issues taken up in two volumes of the Europa XXI journal (nos. 46 and 47) devoted to Current challenges for spatial planning in EU country systems. It proves possible to distinguish between key directions to the research taken up in this context – in relation to spatial planning at the regional and local levels, the conditioning of spatial plans relating to transport, and the incorporation of values into systems of spatial planning. Very strong emphasis is here placed on ways of comparing the solutions and practices applied in what are disparate national systems. If there is no more precise defining of the instruments of spatial planning available at regional level in the states under study, it will be much more difficult to pursue objectives formulated at the EU level (in relation to Member States), as well as to integrate spatial planning with other sectoral policies. A need to continue with research is also noted, especially where that entails attempts to achieve a universal conceptualisation of barriers and challenges put before systems of spatial planning.
29 cm